Aspects of Sustainability: Cooperation, job satisfaction, and burnout among Swiss psychiatrists - Johanna eBaumgardt; Jörn eMoock; Wulf eRössler; Wulf eRössler; Wulf eRössler; Wolfram eKawohl; Wolfram eKawohl (Frontiers Media S.A., 2015)
PurposeGreater sustainability in mental health services is frequently demanded but seldom analyzed. Levels of cooperation, job satisfaction, and burnout are indicators of social sustainability in this field and are of particular importance to medical staff. Because registered psychiatrists play a central role, we assessed the status quo and interactions between these three factors among registered psychiatrists in Switzerland.MethodA postal survey with 3 standardized questionnaires about cooperation, job satisfaction, and burnout was conducted among all registered psychiatrists in the German-speaking part of Switzerland (n = 1485). Addresses were provided by the Swiss Medical Association.ResultsResponse rate was 23.7% (n = 352), yielding a largely male sample (62.8%; n = 218) aged 55.5 ± 8.7 years old. Quantity (47 ± 56.2 contacts over 3 months) and duration (91.1 ± 101.6 minutes per week) of cooperation was found to be diverse depending on the stakeholder. Quality of cooperation was greatest in general practitioners (81.5%) while it was worst in community mental health providers (54.9%). Overall job satisfaction was assessed rather high (3.7 ± 0.8), and burnout rates were below crucial values (Emotional Exhaustion, 2.9 ± 0.8; Depersonalization, 1.9 ± 0.5). Both were positively influenced by cooperation. The strongest correlation was found between job satisfaction and burnout, and both had significant inverse relationships in all dimensions.ConclusionsTo foster sustainability in outpatient mental health care regarding cooperation, job satisfaction, and burnout, personal aspects e.g. age or years of registration, organizational aspects, e.g. networking and practice setting, as wells as supportive aspects e.g. psychotherapy, and self-help groups, must be considered. Quality of cooperation should be reinforced in particular. Because Integrated and Managed Care models cover several of these factors, they should be more strongly embedded in health care systems